PENGARUH VIDEO EDUKASI STUNTING TERHADAP PENGETAHUAN IBU HAMIL TENTANG PENCEGAHAN STUNTING - Pipin, Apriliana; Katharina, Telly; Pramulya, Asmaurina; Ardhana, Putra (Jurnal Keperawatan dan Kesehatan, 2025)
Stunting remains a major public health problem that affects the quality of human resources in Indonesia. The low level of knowledge among pregnant women regarding stunting prevention is one of the factors that exacerbate this condition. This study aims to determine the effect of stunting educational videos on the knowledge of pregnant women about stunting prevention in the working area of Sui Ambawang Health Center. The research design used was a quasi-experimental with a one group pretest-posttest design. The subjects of the study were all pregnant women in the Sui Ambawang Health Center area who received an intervention in the form of a 4-minute educational video. Data were collected through pre-test and post-test questionnaires on knowledge, and analyzed using the Wilcoxon test. The results showed that most respondents were multiparous mothers (76.7%), had a high school education (76.7%), and were housewives (76.7%). Before the intervention, 12 mothers (40%) had low knowledge, while after the intervention, 15 mothers (50%) had good knowledge. The Wilcoxon test showed a p-value of 0.013 (<0.05), indicating a significant effect of the educational video on improving pregnant women’s knowledge about stunting prevention. In conclusion, audiovisual media proved effective in increasing the knowledge of pregnant women, as it can deliver messages in an engaging, clear, and easily accessible manner. Educational videos can serve as an alternative medium in health promotion activities to support the national program for accelerating stunting reduction in Indonesia.